Circadian Health and Light: A Report on the National Heart, Lung, and Blood Institute's Workshop. Issue 5 (October 2018) - Mason, Ivy C.; Boubekri, Mohamed; Figueiro, Mariana G.; Hasler, Brant P.; Hattar, Samer; Hill, Steven M.; Nelson, Randy J.; Sharkey, Katherine M.; Wright, Kenneth P.; Boyd, Windy A.; Brown, Marishka K.; Laposky, Aaron D.; et al.
Despite the omnipresence of artificial and natural light exposure, there exists little guidance in the United States and elsewhere on light exposure in terms of timing, intensity, spectrum, and other light characteristics known to affect human health, performance, and well-being; in parallel, there is little information regarding the quantity and characteristics of light exposure that people receive. To address this, the National Center on Sleep Disorders Research, in the Division of Lung Diseases, National Heart, Lung, and Blood Institute, held a workshop in August 2016 on circadian health and light. Workshop participants discussed scientific research advances on the effects of light on human physiology, identified remaining knowledge gaps in these research areas, and articulated opportunities to use appropriate lighting to protect and improve circadian-dependent health. Based on this workshop, participants put forth the following strategic intent, objectives, and strategies to guide discovery, measurement, education, and implementation of the appropriate use of light to achieve, promote, and maintain circadian health in modern society.